Grammatical Error Of Simple Past Tense In Writing Narrative Text At Student’s Of Economic Syariah - Amir Hamzah (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This research aims to analyzed the grammatical error of simple past tense in writing narrative text at student’s of economic syariah major for the college of Islamic religious Syaichona Moh. Cholil Bangkalan in second semester of academic year 2022-2023 A quantitative research was chosen in this study because the researcher want to know the number of error in Tenses especially in the case of simple past tense that had been given to twenty seven students using a narrative text entitled marriage proposal. In analyzing the data, first the researcher scored the student mastery on writing narrative text by using analytic scoring based on the content of orientation, complication and re-orientation. In each criterion the researcher gives 25 point and the researcher will gives 100 when it got accuratly. Also the researcher use a test and a questionnaire to make ensure the result and after that the researcher found some problem in making narrative text the researcher found some errors in making narrative text.. Besides the errors they made, the researcher had his own opinion based on the result of analyzing their errors. Most of the students made mistakes because of the reasons from the analyzed test: Firstly The student did not fully understand how to make good paragraph. Secondly A little students still had un-unity text. The texts looked like not complete that showed texts that are not done. Thirdly Coherence, which is one of students’ error, had their own mount in their text. Is showed that students still do not understand in making relation of a sentence with the next sentence. Fourthly most error that student made in making text which analyzing is focused in paragraph is completeness. Some of paragraphs they made were uncomplete.